Hubungan Komunikasi Interpersonal Perawat dengan Kepuasan Pasien - Dedeh Hamdiah; Agung Budiyanto (Universitas Faletehan, 2024)
Health service centers in Indonesia were growing and developed rapidly, resulting on many choices in health services that patients can entrust in carrying out their health care. Patients’ expectation when choosing health services was the ability of health staff to respond quickly to patient complaints and to deal with them in a professional manner. The research objective was to determine the relationship between nurse interpersonal communication and patient satisfaction at Pontang Community Health Center in 2023. The correlation method with a cross-sectional approach was used in this research. Of the 150 inpatients as a population, 75 respondents were involved as the samples by Solvin formula. The data collection was done by interviews, observations, and a questionnaire. The research results showed that the majority of respondents stated that the interpersonal communication of nurses was good (62.7%) and the majority of respondents stated that patient satisfaction in the inpatient unit was not satisfied (54.7%). The statistical test results by using chi-square test obtained a p-value of 0.024 (p<α), which means that there was a relationship between nurse interpersonal communication and patient satisfaction at the inpatient unit of Pontang Community Health Center. The researchers concluded that there was a need of reinforcement in inpatient nurses, such as training on interpersonal communication and service excellence.